Imaging simulation of charged nanowires in TEM with large defocus distance. (26th February 2021) - Shi, Te; Liu, Shikai; Tian, H; Ding, Z J
Abstract: In transmission electron microscope (TEM), both the amplitude and the phase of electron beam change when electrons traverse a specimen. The amplitude is easily obtained by the square root of the intensity of a TEM image, while the phase affects defocused images. In order to obtain the phase map and verify the theoretical model of the interaction between electron beam and specimen, a lot of simulations have to be performed by researchers. In this work, we have simulated defocus images of a SiC nanowire in TEM with the method of electron optics. Mean inner potential and charge distribution on the nanowire have been considered in the simulation. Besides, due to electron scattering, coherence loss of the electron beam has been introduced. A dynamic process with Bayesian optimization was used in the simulation. With the infocus image as input and by adjusting fitting parameters, the defocus image is determined with a reasonable charge distribution. The calculated defocus images are in a good agreement with the experimental ones. Here, we present a complete solution and verification method for solving nanoscale charge distribution in TEM.